Mathematics related self-efficacy beliefs and task-motivation and associations with mathematics fluency development : a longitudinal study of children from 1st grade to 2nd grade - Lähtevänoja, Antti; Penttinen, Silja (2018)
There is evidence that self-efficacy and task-motivation in mathematics play a crucial role in regulating mathematical performance. The purpose of this Master’s thesis was to find out how mathematics related self-efficacy and task-motivation develop from 1st to 2nd grade, and are there any differences between gender, parent’s education level groups or mathematical fluency level groups. Furthermore, it was studied how mathematics related self-efficacy and task-motivation are associated with mathematical fluency in 1st grade spring and 2nd grade spring.